2017
DOI: 10.1016/j.jenvp.2017.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Nature exposure predicts well-being trajectory groups among employees across two years

Abstract: We investigated relations between various types of self-reported nature exposure at work and at home, and well-being among employees (N ¼ 664) across two years. An electronic questionnaire was delivered three times, once a year. We identified seven employee groups with different long-term trajectories of four well-being indicators (vitality, happiness, vigor and creativity at work). More frequent physical activity (PA) in natural surroundings during free time in the first measurement increased the odds of belo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 67 publications
0
22
1
3
Order By: Relevance
“…Thus, higher green area proportions around the residency decreased the perceived wellbeing. This is a rather contradictory result compared to previous studies on nature, green space and health [ 48 , 49 ]. These results suggest that the true exposure to green instead of availability of green spaces are important to wellbeing.…”
Section: Discussioncontrasting
confidence: 84%
“…Thus, higher green area proportions around the residency decreased the perceived wellbeing. This is a rather contradictory result compared to previous studies on nature, green space and health [ 48 , 49 ]. These results suggest that the true exposure to green instead of availability of green spaces are important to wellbeing.…”
Section: Discussioncontrasting
confidence: 84%
“…Stress was reduced through shinrin-yoku (Vujcic et al 2017;Morita et al 2007), supporting Stress Reduction Theory (Ulrich et al 1991). The role of nature in affect regulation is often overlooked (Korpela et al 2018), and although not explicitly explored, findings accord with the three emotion regulatory systems model (threat, drive, and soothing; Richardson et al 2016); being in nature may activate our soothing system, endorsing compassion, safety and connection, protecting our mental health. Psychological constructs relevant to the soothing system such as self-compassion and psychological safety need to be examined in shinrin-yoku research.…”
Section: Discussionmentioning
confidence: 65%
“…Evidence of the effects of outdoor green spaces on psychological and mental health is inconsistent. While numerous studies have reported positive associations between access to private green space and psychological and mental health ( Wu et al, 2015 ; Cox et al, 2017 ; Korpela et al, 2017 ; Richardson et al, 2017 ; Dadvand et al, 2019 ; Kruize et al, 2020 ; Spano et al, 2020a ; Giannico et al, 2021 ) and an inverse association between surrounding greenness and depression ( Banay et al, 2019 ), others have found poor evidence on the effect of access to green spaces on mental health in adults and children ( Gascon et al, 2015 ). Still others have reported a stronger association for surrounding greenness than for access to green spaces with mental health ( Triguero-Mas et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%